Evaluating Student Needs for Engaging English Speaking Programs within the English Day Framework - Ziyyanida Musafiroh; Rizka Safriyani; Khoiril (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This research examines the needs of students enrolled in English-speaking programs, with a particular emphasis on their preferences and levels of engagement in various themed activities during the English Day program. Proficiency in speaking is essential for achieving fluency in English; however, it poses significant challenges for numerous students. The study employs a quantitative survey approach to evaluate student participation in eight distinct speaking activities, including role-playing, group discussions, and film discussions, within the contexts of Nutritious Friday, Healthy Friday, Cleanliness Friday, and Religious Friday themes. Data collected from sixty participants were analyzed using descriptive statistical techniques, focusing on preferences for activities based on frequency, percentage, mean, and standard deviation. The findings indicate that students favour activities such as film discussions and word games, which provide visual stimulation and a relaxed, low-pressure atmosphere. Conversely, more formal speaking tasks, including debates and presentations, garnered less engagement, highlighting the necessity for confidence-building measures before engaging in structured speaking exercises. These insights are instrumental in shaping an English-speaking curriculum that caters to student needs, fostering regular use of English, supportive social settings, teacher assistance, and various speaking activities across different themes. The recommendations derived from this study are intended to assist educators in creating effective, student-focused English-speaking programs that resonate with students' interests and levels of thematic engagement.